The little book of venture capital investing : empowering economic growth and investment portfolios - Gerken, Louis, 1925- (Little book big profits., 2014)
A little book full of enormous value for novices and seasoned venture capitalists alikeAfter having been thrown for a loop by the bursting of the tech bubble more than a decade ago, the venture capital industry suddenly has come roaring back to life over the past two years. In 2011 alone, more than $7.5 billion in venture capital was invested--representing more than a 19% increase over the previous year--in more than 966 companies. A majority of these companies reside in the life sciences, Internet, and alternative energy sectors. In today's weak job market, VC is more important than ever, since financing new tech, alternative energy, media, and other small to mid-sized companies is vital to creating new jobs. Written by Lou Gerken, a noted international authority on venture capital and alternative investments, this book tells you everything you need to ... The EPUB format of this title may not be compatible for use on all handheld devices.